Molahidatidosa from Pathophysiology to Clinical: Literature Review - Hidayat, Rachmat; Irawan Sastradinata (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
A B S T R A C THydatidiform is a gestational trophoblast disease which is histopathologicallycharacterized by the proliferation of avascular trophoblast cells and corial villi andundergoing hydrophic degeneration. The proliferation of trophoblast cells inhydatidiform moles can be in the form of cytotrophoblast, syncytiotrophoblast orintermediate trophoblast proliferation.